The use of Concept Maps as an evaluative resource in the theme Acid Rain in Higher Education - Felipe Alves Silveira; Ana Karine Portela Vasconcelos (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The elaboration of Conceptual Maps - CM contributes to identifying signs of meaningful learning - ML, as it is an instrument to represent the acquired knowledge. The present investigation aims to analyze the use of the CM tool in teaching during the initial education of chemistry teachers as an evaluative instrument regarding the topic of acid rain, having as input the Theory of Meaningful Learning - TML. In the research, we seek to approach concepts related to the inorganic functions of acids and oxides through an investigative experiment. The methodological field is a qualitative approach based on the case study. We conclude that the CM is configured as a satisfactory evaluative instrument because, during their structuring and restructuring, some cognitive conflicts and spaces raise awareness of the problems, difficulties, and errors that, confronted and discussed, become spaces for advancing knowledge understanding.